Peran Kepemimpinan Kepala Sekolah dalam Penerapan Program Program Merdeka Belajar di Sekolah - Farsya Salsabila Putri; Muhammad Roisul Basyar (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
The Headmaster has a role and responsibility in the continuity of education within the school. In the world of education, there are always different times and curricula that are constantly evolving. A leader must also adapt to new learning systems and curricula. The Merdeka curriculum itself is a manifestation of the adaptation of the previous era. In this curriculum, educators are given the freedom to provide quality learning according to the needs and learning environment for students. The Merdeka curriculum itself is designed by the government to address learning crises and improve the quality of learning in all educational units. The method used in this study is descriptive qualitative with data analysis techniques consisting of data collection, interviews, and drawing conclusions. This study aims to see how a leader carries out the responsibility in implementing the Merdeka curriculum and the challenges in implementing the Merdeka curriculum. With this research, the author hopes to understand the role of school leadership in implementing the Merdeka curriculum.